2021
DOI: 10.1083/jcb.202003149
|View full text |Cite
|
Sign up to set email alerts
|

CEP55 promotes cilia disassembly through stabilizing Aurora A kinase

Abstract: Primary cilia protrude from the cell surface and have diverse roles during development and disease, which depends on the precise timing and control of cilia assembly and disassembly. Inactivation of assembly often causes cilia defects and underlies ciliopathy, while diseases caused by dysfunction in disassembly remain largely unknown. Here, we demonstrate that CEP55 functions as a cilia disassembly regulator to participate in ciliopathy. Cep55−/− mice display clinical manifestations of Meckel–Gruber syndrome, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
20
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(23 citation statements)
references
References 60 publications
(92 reference statements)
1
20
0
Order By: Relevance
“…Tedeschi et al [ 8 ] and our Cep55 knockout mice were generated using ES clones from the European mutant mice consortium, albeit using different clones (HEPD0726_6_A04; HEPD0726_6_B01). Both studies generated a tm1a allele, in C57BL/6 genetic background, but there could be substrain differences, whereas the other two studies generated mice using CRISPR-Cas9 in either a mixed C57BL/6 and FBV/N or pure C57BL/6 background [ 9 , 10 ]. These prior studies, also reported slight differences in postnatal lethality ranging from preweaning lethality with incomplete penetrance, ~7% homozygous mice viable between (P1- P14) to 100% mortality for KO pups at P2 [ 8 , 9 ].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Tedeschi et al [ 8 ] and our Cep55 knockout mice were generated using ES clones from the European mutant mice consortium, albeit using different clones (HEPD0726_6_A04; HEPD0726_6_B01). Both studies generated a tm1a allele, in C57BL/6 genetic background, but there could be substrain differences, whereas the other two studies generated mice using CRISPR-Cas9 in either a mixed C57BL/6 and FBV/N or pure C57BL/6 background [ 9 , 10 ]. These prior studies, also reported slight differences in postnatal lethality ranging from preweaning lethality with incomplete penetrance, ~7% homozygous mice viable between (P1- P14) to 100% mortality for KO pups at P2 [ 8 , 9 ].…”
Section: Discussionmentioning
confidence: 99%
“…Both studies generated a tm1a allele, in C57BL/6 genetic background, but there could be substrain differences, whereas the other two studies generated mice using CRISPR-Cas9 in either a mixed C57BL/6 and FBV/N or pure C57BL/6 background [ 9 , 10 ]. These prior studies, also reported slight differences in postnatal lethality ranging from preweaning lethality with incomplete penetrance, ~7% homozygous mice viable between (P1- P14) to 100% mortality for KO pups at P2 [ 8 , 9 ]. We observed a significant reduction in the numbers of KO pups obtained at P0 compared to the expected number based on Mendelian ratio.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…PLK1 has also been implicated in protein trafficking by phosphorylating the transition zone protein nephrocystin-1 [ 84 ]. Centrosomal protein of 55 kD (CEP55) is shown to facilitate the recruitment of chaperonin containing TCP1 chaperonin complex to AurA, stabilizing AurA and promoting ciliary disassembly [ 85 ]. Studies from our lab have shown that the centrosomal integrity/mitotic surveillance (CI) pathway comprising USP28, p53, and 53BP1 plays a significant role in cilia disassembly downstream of polycystin genes ( Pkd1 or Pkd2 ) [ 43 ].…”
Section: Cilia Disassembly and Its Regulationmentioning
confidence: 99%